A general method for asymmetric arylation and vinylation of silyl ketene acetals - Yang, Junfeng (2018)
A new biarylmonophosphine was developed for highly asymmetric arylation and vinylation of silyl enolates of acyclic esters with good generality. The new stereocenters α to the ester groups were formed in high enantiomeric excess. The method was applied to the asymmetric synthesis of Profen drugs on a gram scale.